MODERN AL-IKHWAN ISLAMIC BOARDING SCHOOL EDUCATION SYSTEM IN PADANG TUALANG LANGKAT - Muhammad Supawi, Abd. Mukti, Syamsu Nahar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: The main problem in this research is the education system of Al-Ikhwan’s new Islamicboarding school in Padang Tualang Subdistrict. This study aims to find out the education system ofAl-Ikhwan Modern Islamic Boarding School in Padang Tualang District of Langkat Regency. Thisstudy uses a qualitative approach with a descriptive phenomenological and analytical method byprocessing graphic data sources compiled from research informants, both secondary and primarydata obtained through an interview process to the research informants. In data processing, reduction,encoding, and editing of existing documents are then presented in the form of data displays. Then aconclusion is drawn from the entire research process. The research instrument is the researcherhimself (Human Instrument) supported by observation guidelines, interview guidelines. Data is takenfrom various sources that support the objectives of this study.